A consideration regarding phenomenological movement theory in gymnastics: backward giant swing on horizontal bar - Yamashita, R.; Morii, D. (Japan Journal of Physical Education, Health and Sport Sciences, 2024)
Skills in sports occurred and developed based on subjective method such as consciousness and sense within the performers. Sports skills are not unchanging elements and they change shape and evolve with the times. Backward giant swing on horizontal bar in gymnastics is an extremely important basic skill as mastering level of such skill directly relates to the standard of horizontal bar performance. A conventional theory of this skill is spread both nationally and internationally and such theory suggests that rotational acceleration is created by snapping which requires breaking shoulders and maximizing extension and flexion of body joint to tap the body to the limit. In contrast, a world`s highest-level performer who is the subject of the current study argued that it is staying tight rather than breaking which is completely different knack to the commonly known theory. Technical characteristics and significance of this performer were elucidated by category analysis of phenomenological movement theory. The analysis revealed that the world`s highest-level performer creates rotational acceleration by using a reaction of horizontal bar which is produced by maximizing a bounce of the bar. Such reaction of the bar is produced by generating tension in the body during overhang phases by staying tight to stop shoulders, waist and chest from extending.